Determinants of the Entrepreneurial Intention of Private Sector Employees in the Age of Disruption: The Role of Saving Behavior as a Mediating Variable - Gaguk Tri Prasetyo; Muhammad M. Hakim; Joko Setiawan (Universitas Negeri Semarang, 2026)
This study aims to examine the determinants of entrepreneurial intention among employees in private companies in Indonesia by integrating financial and psychological factors through a mediating mechanism. Data were collected through a survey with 209 valid responses and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that financial literacy and financial efficacy significantly influence entrepreneurial intention, both directly and indirectly through saving behavior. In contrast, perceived job insecurity does not have a significant effect on entrepreneurial intention. Saving behavior is found to play a crucial role as it not only directly affects entrepreneurial intention but also mediates the relationship between financial literacy and financial efficacy with entrepreneurial intention. However, saving behavior does not mediate the relationship between perceived job insecurity and entrepreneurial intention. These findings highlight the importance of financial capability factors over psychological job-related concerns in fostering entrepreneurial intention among employees.